Система двох частинок у некомутативному просторi зi збереженою сферичною симетрiєю - Gnatenko, Kh. P.; Tkachuk, V. M. (Publishing house "Academperiodika", 2019)
We consider a system of two particles in the noncommutative space, which is rotationally invariant. It is shown that the coordinates of the center-of-mass position and the coordinates of relative motion satisfy a noncommutative algebra with corresponding effective tensors of noncommutativity. A hydrogen atom is studied as a two-particle system. We have found the corrections to the energy levels of the hydrogen atom up to the second order in the parameter of noncommutativity.